1990
DOI: 10.1037/0096-1523.16.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Lexical effects in phonemic processing: Facilitatory or inhibitory?

Abstract: This article addresses the questions of how and when lexical information influences phoneme identification in a series of phoneme-monitoring experiments in which conflicting predictions of autonomous and interactive models were evaluated. Strong facilitatory lexical effects (reflected by large differences in detection latencies to targets in words and matched nonwords) were found only when targets came after the uniqueness point of the target-bearing word. Furthermore, no evidence was obtained for lexically me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
4
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(141 citation statements)
references
References 33 publications
8
126
4
3
Order By: Relevance
“…If the comprehension system reacts to the incoming phonological representation in the same way as it reacts to an acoustic speech signal, then the speed-up in processing for word-final phonemes (which would occur after the word's uniqueness point, see Frauenfelder et al, 1990) may be a comprehension effect. In other words, responses to word-final phonemes may be based on phonological information made available following lexical access in the comprehension lexicon.…”
Section: Discussionmentioning
confidence: 99%
“…If the comprehension system reacts to the incoming phonological representation in the same way as it reacts to an acoustic speech signal, then the speed-up in processing for word-final phonemes (which would occur after the word's uniqueness point, see Frauenfelder et al, 1990) may be a comprehension effect. In other words, responses to word-final phonemes may be based on phonological information made available following lexical access in the comprehension lexicon.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [46,47] failed to find any slowing effect for contextually inconsistent phonemes, casting doubt on interactive processing. However, subsequent simulations showed that the TRACE model was consistent with previous failures to demonstrate this effect and correctly predicted the conditions required to show lexical inhibition [17].…”
Section: Lexical Inhibition Of Phoneme Recognitionmentioning
confidence: 99%
“…Marslen-Wilson 1987), though certain factors such as semantic/syntactic context (Zwitserlood 1989) or word frequency can additionally affect the position of the recognition point. Contrary to predictions of alternative theories, such as the connectionist model TRACE by Elman/McClelland (1984), there is no evidence that activated competitors actively inhibit one another (Frauenfelder/Segui/Dijkstra 1990).…”
Section: Phonological Decodingmentioning
confidence: 59%
“…Though there is good evidence that a word's acoustic-phonetic processing is not affected by lexical or higher level processes (Frauenfelder/Segui/Dijkstra 1990), the effects of context on word recognition have been heavily debated. It is rather safe now to say that when a speaker hears an ambiguous word (like bank), both of its meanings are temporarily retrieved from the lexicon, even if one is ruled out by the context (as in / withdrew my money from the bank) (Seidenberg/Tanenhaus/Leiman/Bienkowski 1982).…”
Section: Incrementality Autonomy and Interactionmentioning
confidence: 99%